Differences in oxidative potential of black carbon from three combustion emission sources in China. (15th June 2019) - Li, Rong; Han, Yong; Wang, Lu; Shang, Yu; Chen, Yingjun
Abstract: Black carbon (BC) is mainly derived from the incomplete combustion of fossil fuels and biomass, and poses a serious threat to human health. Actual BC from extensive emission sources presents a variety of characteristics that are likely associated with different oxidative potentials (OP) and health endpoints. In the present study, BC derived from three main emission sources (residential coal combustion, biomass burning, and diesel engine exhaust) in China was subjected to physiochemical characterization and its OP was tested using dithiothreitol (DTT) assay. In order to obtain actual BC, the water-soluble part (WS) and organic extract (OE) were eluted successively from PM and the residue particle (RP) were reserved. PM from diesel vehicles had the most effective DTT consumption capacity, followed by PM from biomass and coal burning. And the OP of PM was mostly attributed to its RP part which mainly consisted of metals and BC. SEM/TEM, OC/EC, IC, and ICP-MS measurements confirmed that soluble ions and organic compounds were washed off effectively, while some metals were still retained in the RP part. Thus, the OP of BC was evaluated after adding DTPA to inhibit DTT activity caused by metals in the RP. Significant differences in OP and physiochemical characteristics of BC from the three emission sources were observed. BC from diesel exhaust exhibited the highest DTT activity (15.5 ± 12.6 pmol min −1 μg −1 ) compared to that of BC from biomass (2.5 ± 1.0 pmol min −1 μg −1 ) and coal (1.3 ± 0.5 pmol min −1 μg −1 ) burning. Diesel exhaust BC, which was emitted under the highest combustion temperature, had the smallest size. Coal consumption in China contributes to the highest amount of BC mass emission, but our result indicates that diesel exhaust BC has the greatest OP. An emission inventory based on health impacts is urgently needed to control air pollution sources in the future. Graphical abstract: Image 1 Highlights: Real source BC shows DTT activity and contributes greatly to the OP of PM. BC from various combustion sources shows different OPs. Diesel exhaust BC presents the smallest size and the highest DTT activity among coal, biomass and diesel samples.